2019
DOI: 10.36085/jkmu.v7i2.418
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Air Rebusan Daun Sirih Merah terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Saling 2018

Abstract: Diabetes Melitus merupakan penyakit kronik yang terjadi akibat pankreas tidak mampu menghasilkan insulin yang cukup atau ketika tubuh tidak dapat secara efektif menggunakan insulin tersebut. Tujuan penelitian ini adalah untuk mempelajari efektivitas pemberian air rebusan daun sirih merah terhadap penurunan kadar gula darah pasien Diabetes Melitus di Wilayah Kerja Puskesmas Saling Kabupaten Empat Lawang Tahun 2018. Desain penelitian ini adalah Quasy eksperimental dengan menggunakan rancangan The One Group Prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
4
0
7
Order By: Relevance
“…The red betel leaf (Piper crocatum) has been reported as a useful herbal medicine in some diseases, particularly diabetes mellitus [27]. It contained phytochemical compounds of alkaloid, flavonoid, and tannin groups, which have antihyperglycemic, antioxidant, and antidiabetic properties [28]. The previous study also demonstrated that boiled red betel leaf administration was effectively reduced the blood sugar levels of T2DM patients without complications [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The red betel leaf (Piper crocatum) has been reported as a useful herbal medicine in some diseases, particularly diabetes mellitus [27]. It contained phytochemical compounds of alkaloid, flavonoid, and tannin groups, which have antihyperglycemic, antioxidant, and antidiabetic properties [28]. The previous study also demonstrated that boiled red betel leaf administration was effectively reduced the blood sugar levels of T2DM patients without complications [28].…”
Section: Discussionmentioning
confidence: 99%
“…It contained phytochemical compounds of alkaloid, flavonoid, and tannin groups, which have antihyperglycemic, antioxidant, and antidiabetic properties [28]. The previous study also demonstrated that boiled red betel leaf administration was effectively reduced the blood sugar levels of T2DM patients without complications [28]. Reactive Oxygen Species (ROS) produced from streptozotocin-nicotinamide induction cause oxidative stress including protein denaturation, lipid peroxidation, and DNA damage [6].…”
Section: Discussionmentioning
confidence: 99%
“…Menurut peneliti Listiana, Effendi, and Indriati (2019)didapatkan bahwa sebagian besar dari responden penderita Diabetes Melitus tidak mengetahui manfaat atau kegunaan dari daun sirih merah. Daun sirih merah merupakan pengobatan alternatif yang lebih baik, alamiah, murah mudah didapat dengan efek minimal untuk menurunkan kadar gula darah.…”
Section: Hasil Dan Pembahasanunclassified
“…Selain itu terdapat pula senyawa lain seperti hidroksikavikol, kavikol, kavibetol, karvakol, eugenol, p-simen, sineol, kariofilen, kadimen estragol, terpenena dan fenil propanoid (Novilia et al, 2018;Parfati et al, 2016). Kandungan senyawa dari golongan flavonoid daun sirih merah yang diduga memiliki aktifitas sebagai antiinflamasi adalah toksifolin, brazilin, haematoksilin, gosipin, prosianidin dan nepritin (Jouad et al, 2001;Listiana et al, 2019). Berdasarkan Tabel 1 diketahui daun sirih merah mengandung senyawa bioaktif berupa flavonoid, saponin, tanin, alkaloid, steroid/terpenoid, antarkinon dan fenol (Maslikah et al, 2019).…”
Section: Penggunaan Daun Sirih Merah Secara Empirisunclassified